Positive but also negative effects of ethnic diversity in schools on educational performance? An empirical test using PISA data - Jaap Dronkers; Rolf van der Velden (Centre for Research & Analysis of Migration (CReAM), Department of Economics, University College London, 2012)
In this chapter, we will estimate the effects on language skills of two characteristics of school populations: average/share and diversity, on both the ethnic and the sociocultural dimensions. We will use the cross-national Program for International Student Assessment (PISA) 2006 data for native students and students with an immigrant background, in which both cohorts are 15 years old. A greater ethnic diversity of school populations in secondary education hampers the educational performance of students with an immigrant background but does not significantly affect that of native students. The sociocultural diversity of schools has no effect on educational performance. However, the level of the curriculum attended by the students and the average parental sociocultural status of schools are important variables that explain the educational performance of children. A higher share of students of non-Islamic Asian origin in a school increases the educational performance of both native and immigrant students of other origins in that school. Students from non-Islamic Asian countries in schools with higher shares of students of non-Islamic Asian origin perform better than do comparable students originating from other regions. Students originating from Islamic countries have substantially lower language scores than do equivalent students with an immigrant background from other regions. This cannot be explained by individual socioeconomic backgrounds, school characteristics, or educational systems.
Keywords: 330